Lingual thyroid: can we 'wait and see'?. (3rd August 2015) - Magalhães, Clara; Azevedo, Paula; Nakamura, Roberto; Duarte, Delfim
Abstract : A 42-year-old Caucasian woman presented with a sensation of fullness in the throat and dry cough of 1-month duration. Physical examination showed a mass located in the midline of the tongue base. Cervical ultrasound confirmed the absence of thyroid gland tissue in the normal position. MRI of the neck showed a mass suggestive of lingual thyroid and scintigraphy confirmed the diagnosis. Thyroid function was normal. Despite normal thyroid function, to decrease the size of the mass and perhaps solve the problem, we decided to start levothyroxine suppression therapy. The patient had palpitations and one episode of angina pectoris as a side effect, resulting in the medication being interrupted. After 3 years of follow-up, she remains in clinical surveillance and without symptoms.